ANALISIS PRODUKTIVITAS DAN PROFIL INDUSTRI GULA KELAPA DI DESA GUMELEM KULON KABUPATEN BANJARNEGARA - Sri Hidayati (Universitas Muhammadiyah Purwokerto, 2007)
The aim of this research was to know : (a) craftsman’s profile of coconut sugar industry, (b) identity and analyze of production factors, (c) level of total productivity, average product, average revenue, and marginal product. The research was conducted at village of Gumelem Kulon, Kecamatan Susukan, Kabupaten Banjarnegara. The sampling method was simple random sampling takers 30 craftsman respondents. The result of the research show that coconut sugar industry are hereditary household industry and interconnected to existense of community social. The craftsman’s profile with specification the number of some coconut crops, the low formal study basic and the long time experience of interpreneuring, low capital, the feasibility of having the row material (nira), woods and labor, and the traditionally skill of managing coconut sugar industry, the price determining which tends to determined unilateral, the marketing system generally done by the craftsman through the broker, market, small shop and cooperative. The production factors. Which affecting is the nira, woods and the labor. Total productivity of equal to 1,92. Average product of equal to : nira = 0,17399 ; woods = 19,8235 ; labor = 4,7722. Average revenue of equal to : nira = 6,30205 ; woods = 2,0318 ; labor = 1,2209. Marginal product of equal to : nira = 0,``48 ; woods = 14,5303 ; labor = 47,1690. Key word : coconut sugar, profile, productivity